Microbial phylogeny and evolution : concepts and controversies - Sapp, Jan (OUP E-Books., 2005)
The extent of lateral gene transfer among diverse microbes has effectively broken down the concept of species when we seek to apply it to the microbial world. This book brings together workers to try to reach an accomodation and consensus on the outline of how cellular life has evolved.